Examination of the diversity in pumpkin (Cucurbita maxima L.) growth accessions in south-eastern Nigeria - Umeh, O. A.; Ani, C. Q.; Ulasi, J. I.; Umeh, I. S.; Keyagha, E.R. (Archives of Agriculture and Environmental Science, 2024)
The aim of the study was to compare the growth rates of various pumpkin (Cucurbita maxima L.) accessions. Pumpkins from Aku I, Aku II, Awka, Ifite-Ogwari Nsukka I, and Nsukka II were the various accessions. A field study was conducted at the Ifite-Ogwari Campus of Nnamdi Azikiwe University in Anambra State. The experiment was laid out using a completely randomized design (CRD) with three replications. As experimental sample units, two (2) of the middle-most plants in each polybag were cut off and tagged. Analysis of Variance (ANOVA) was used to analyze data on vegetative growth factors at a 5% probability level and the treatment means were divided using the least significant difference (LSD 0.05). The result of the experiment revealed that all of the pumpkin accessions performed similarly in terms of the amount of time it took for them to emerge after sowing, their percentage of emergence, and their overall vegetative growth. None of the accessions were statistically different with respect to their emergence and growth parameters. However, the growth parameter evaluations were dominated, on average, by pumpkin accession from Nsukka (I and II) pumpkins. In addition, the Aku II pumpkin had the shortest days-to-emergence (3.33 days) and the greatest mean percentage of emergence (100%). Conversely, Aku I pumpkin consistently performed the lowest when it came to the factors that were looked at. For a comprehensive characterization of C. maxima, additional research at the molecular and genomic levels is advised including a greater number of accessions.